OPTIMALISASI PERSEDIAAN BAHAN BAKAR MINYAK INDUSTRI (SOLAR) PADA PT. PRIMA SENTOSA ALAM LESTARI MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Santi, Santi; Jaya, A I; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2019)
PT. Prima Alam Lestari Sentosa is a company engaged in six areas such as transporter fuel, industrial fuel agents pertamina, SPPBE, general construction services, mining contractor, and the procurement of goods and services. In carrying out its production activity is associated with supplies of fuel oil. Where inventory is one of management activities related to storage costs and reservations so that the necessary optimization of inventory. In this study the authors using Economic Order Quantity to optimize the inventory. This study aims is to determine the inventory optimization of fuel oil at PT. Prima Alam Lestari Sentosa and compared it with the fuel inventory optimization EOQ method. . PT Prima Alam Lestari Sentosa set the amount every one reservations is 14212.50 liters with the number of bookings 317 timeseach year and the total cost of supply is ð‘…ð‘. 710.304.976,352,- while when using the EOQ method, the ordering amount is 20.225 liters with the number of bookings are as 223 times each year and the total inventory cost ð‘…ð‘. 668.280.488,26,-. Thus, in the year of 2016, it is about that the company's policy when using the EOQ method is equal to ð‘…ð‘. 24.024.488,092.Keywords : EOQ Method, Inventory, Optimization.